Diagnostic testing: a key component of high-value care - Lucien J. Cardinal (Greater Baltimore Medical Center, 2016)
This is the fourth article of a series on fundamental concepts in biostatistics and research. In this article, the author reviews the fundamental concepts in diagnostic testing, sensitivity, and specificity and how they relate to the concept of high-value care. The topics are discussed in common language, with a minimum of jargon and mathematics, and with clinical examples. Emphasis is given to conceptual understanding. A companion article will follow focusing on predictive value and prior probability.